Forensic engineering diagnosing failures and solving problems : proceedings of the 3rd International Conference on Forensic Engineering diagnosing failures and solving problems : London, UK, 10-11 November 2005 - Neale, B. S. (Balkema proceedings and monographs in engineering, water and earth sciences., 2005)
Contains papers prepared for the Institution of Civil Engineers' Third International Conference on Forensic Engineering, which focused on diagnosing failures of the built environment with a view to solving problems. The topics in this book are grouped according to the type of incident investigation.